2017
DOI: 10.1063/1.4993135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crystallization interfaces on irradiated ferroelectric thin films

Abstract: This work investigates the role of crystallization interfaces and chemical heterogeneity in the radiation tolerance of chemical solution-deposited lead zirconate titanate (PZT) thin films. Two sets of PZT thin films were fabricated with crystallization performed at (i) every deposited layer or (ii) every three layers. The films were exposed to a range of 60Co gamma radiation doses, between 0.2 and 20 Mrad, and their functional response was compared before and after irradiation. The observed trends indicate enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…For example, Heiroth et al have reported that crystallization temperatures can be decreased by annealing amorphous thin films, compared with directly depositing highly crystalline thin films by PLD . Crystallization studies of piezoelectric lead zirconate titanate thin films and ionically conducting yttria-stabilized zirconia (YSZ) , or ceria-based thin films have focused on the crystallization kinetics and thermally driven microstructural evolution, including microstrain and grain growth kinetics and stagnation …”
Section: Introductionmentioning
confidence: 99%
“…For example, Heiroth et al have reported that crystallization temperatures can be decreased by annealing amorphous thin films, compared with directly depositing highly crystalline thin films by PLD . Crystallization studies of piezoelectric lead zirconate titanate thin films and ionically conducting yttria-stabilized zirconia (YSZ) , or ceria-based thin films have focused on the crystallization kinetics and thermally driven microstructural evolution, including microstrain and grain growth kinetics and stagnation …”
Section: Introductionmentioning
confidence: 99%
“…The good performance of traditional perovskite-based ferroelectric memory (FeRAM) in extreme environments makes it promising for aerospace and nuclear applications. [8][9][10][11][12] Hence, the space applications of the emerging hafnium-based FeRAM are also of interest. It is necessary to systematically evaluate the radiation effects of its materials, devices, and circuits before its application.…”
mentioning
confidence: 99%
“…The γ‐ray radiation will induce trapped defects and compensate a part of internal defects, resulting in a weakened domain unpinning effect. Meanwhile, the radiation effect should be influenced by domain size, orientation, grain boundary density, and morphology, as reported by Brewer et al The different ratios of phase structure and grain boundary in HfAlO‐20 thin films may induce a relative change during fatigue tests, as shown in Figure c.…”
Section: Resultsmentioning
confidence: 68%